BIOMIMCRY AND MANAGEMENT: A STUDY - Gopan, Parvathy S; Jeenu S (International Journal of Research -GRANTHAALAYAH, 2025)
Biomimicry, the practice of emulating nature’s strategies, offers innovative solutions across marketing, management functions, human resource management (HRM), logistics, and supply chain management. This review highlights how biomimicry principles—adaptability, interdependence, efficiency, and resilience—can address key business challenges while promoting sustainability. In marketing, biomimicry enhances customer-centric strategies through insights from ecosystems’ interconnectedness. Management functions and HRM benefit from collaborative structures inspired by natural systems, fostering resilience and fluid adaptability. Logistics and supply chain management draw parallels to biological networks to optimize efficiency and seamless operations. By integrating biomimicry, organizations can redefine their approaches to performance, sustainability, and ethical responsibility. Nature-inspired practices not only address immediate challenges but pave the way for innovative and future-oriented strategies that balance economic, environmental, and social priorities. This review underscores the transformative potential of biomimicry in reshaping industries to align with sustainable principles, fostering long-term success and ecological harmony.